Analisis pengaruh tebal plat terhadap karakteristik mekanik pegas daun pada prototipe mobil fish car unej (fcu) mudskip - Khoirur Rohman; Rika Dwi Hidayatul Qoryah; Aris Zainul Muttaqin; Santoso Mulyadi (Jurnal Teknosains, 2021)
Fish Car Unej (FCU) Mudskip is a car designed with a rural terrain system, especially for fishing transportation. FCU Mudskip uses leaf spring suspension at the rear to support the weight of the vehicle, that is leaning towards the rear. The load of the vehicle is inclined to the rear due to the car carrying system in the form of fish and water. This conveying system can cause leaf spring failure. Therefore, this study aims to determine the value of stress, strain and cycle on leaf springs. Ansys 18.1 software was used to obtain stress, strain, and leaf spring cycle values with a thickness of 7 mm, 10 mm, and 13 mm. The value of stress on leaf springs with thickness 7 is 124,31 x 106 N/m2; thickness 10 mm is 74,92 x 106 N/m2; thickness 13 mm is 48,08 x 106N/m2; the value of strain on leaf springs with a thickness of 7 mm is 0,00075; a thickness of 10 mm is 0,00045; a thickness of 13 mm is 0,00029; Acceptable cycles of leaf springs are 7 mm thick is 69206 cycles, 10 mm is 77833 cycles, and 13 mm thick is 93054 cycles. Leaf springs with a thickness of 13 mm are the most optimal leaf springs because they can receive the most cycles of 93054 cycles, according to the function of leaf springs as vibration dampers.